Experiences of coping with illness in hospitalized patients in Ibagué-Tolima (2023)
We sought to identify the experiences of coping with illness in patients of the Hospitalization services on the floor and the Coronary Intensive Care Unit of a Clinic in Ibagué (Tolima). Materials and Methods: With a qualitative approach, 2 instruments were applied to 15 male and female patients, between the ages of 25 and 78 years old, who experienced different chronic pathologies. Results: The patients' coping experiences show the existence of repertoires of action and omission regarding coping and care of the disease, and wellbeing practices. Categories about worries, what is difficult, what is beautiful, what helps to cope with the disease, what helps to wellbeing and projections of desire when overcoming the hospitalization crisis were made explicit. Discussion: The rupture with ways of life is one of the main difficulties, which, added to the disease, uncertainty and the quality of the hospital service generates favorable or unfavorable conditions for coping. Conclusions: Being able to identify the coping strategies of patients within the hospitalization time can have a positive or negative influence on their recovery. It is relevant to recognize and give place to the knowledge and practices from the voice of the patients themselves, in order to generate coherent and respectful actions with different ways of living, caring and dying.